2016
DOI: 10.2147/ijn.s112030
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous silica nanoparticles trigger vascular endothelial cell injury through apoptosis and autophagy via reactive oxygen species-mediated MAPK/Bcl-2 and PI3K/Akt/mTOR signaling

Abstract: Environmental exposure to silica nanoparticles (SiNPs) is inevitable due to their widespread application in industrial, commercial, and biomedical fields. In recent years, most investigators focus on the evaluation of cardiovascular effects of SiNPs in vivo and in vitro. Endothelial injury and dysfunction is now hypothesized to be a dominant mechanism in the development of cardiovascular diseases. This study aimed to explore interaction of SiNPs with endothelial cells, and extensively investigate the exact eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(124 citation statements)
references
References 81 publications
4
111
1
1
Order By: Relevance
“…N‐acetyl‐cysteine can prevent JNK phosphorylation in human gastric carcinoma MKN45 cells (Guo et al, ) and can reverse the overexpression of p38‐associated pathways in vascular endothelial cells (Bhattacharya, Halder, Mukhopadhyay, & Giri, ) and human melanoma cells (Bell et al, ). It has been reported that Pin was isolated from the gorgonian coral Pinnigorgia sp., which triggered the activated HSCs to undergo apoptosis via ROS‐ERK/JNK‐caspase‐3 signaling and probably caused the clearance of HSCs (Kuo et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N‐acetyl‐cysteine can prevent JNK phosphorylation in human gastric carcinoma MKN45 cells (Guo et al, ) and can reverse the overexpression of p38‐associated pathways in vascular endothelial cells (Bhattacharya, Halder, Mukhopadhyay, & Giri, ) and human melanoma cells (Bell et al, ). It has been reported that Pin was isolated from the gorgonian coral Pinnigorgia sp., which triggered the activated HSCs to undergo apoptosis via ROS‐ERK/JNK‐caspase‐3 signaling and probably caused the clearance of HSCs (Kuo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…N-acetyl-cysteine can prevent JNK phosphorylation in human gastric carcinoma MKN45 cells (Guo et al, 2016) and can reverse the overexpression of p38-associated pathways in vascular endothelial cells (Bhattacharya, Halder, Mukhopadhyay, & Giri, 2009) and human melanoma cells (Bell et al, 2010). It has been The experiments were independently repeated three times (n = 3).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of autophagy was demonstrated in the alveolar macrophages of silicosis mouse model [49] and in the cultured alveolar macrophages exposed to silica [50][51][52][53] in response to silicon toxicity; autophagy is an important pro-survival mechanism for maintaining metabolic homeostasis under stress [54, [56]. Positive immunolabeling for LC-3 (an marker of autophagy) and LAMP-1 www.fhc.viamedica.pl (a lysosome marker) was also observed in the cytoplasm of enlarged macrophages containing fine ASD particles; positive LC-3 staining was less prominent in low level serum Zn mice, suggesting that autophagy was being blocked as a result of Zn deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy of VSMCs and endothelial cells can be triggered by inflammatory mediators, ROS, oxLDL, TNF-α and osteopontin. There is evidence indicating that NPs trigger the autophagy process in vascular endothelial cells [14], while it remains unknown whether PMs could regulate autophagy in cardiovascular cells.…”
Section: Autophagymentioning
confidence: 99%